GC-MS analysis of chemical constituents and in vitro antioxidant activity of the organic extracts from the stem of Bridelia stipularis - Samina Khan Yusufzai; Mohammad Shaheen Khan; Eunice Lua Hanry; Mohd. Rafatullah; Belsheera Elison (Penerbit UKM, 2019)
In the present study the stems of the Bridelia stipularis (L.) Blume, which is traditionally used by ethnic communities in Sabah, Malaysia, has been investigated for its chemical composition, total flavonoid content (TFC) and total phenolic content (TPC) via Gas-Chromatography-Mass Spectroscopy (GC-MS) analysis consuming hexane, chloroform and ethyl acetate as extraction solvents and gallic acid and quercetin as internal standards. In vitro antioxidant activity (AA) was determined by the application of 1,1-diphenyl-2-picryl hydrazine (DPPH) radical scavenging assay using tert-butyl-1-hydroxytoluene (BHT) as comparative drug. The GC-MS profiling showed the presence of 1-dodecanol (40.917%), oxalic acid, cyclobutyl octadecyl ester (24.985%), 1-octanol,2-nitro (12.424%), benzaldehyde, 2,4-dimethyl- (9.583%), 4-tridecanol (6.359%) and nitric acid, nonyl ester (5.616%) as major constituents. The TPC (224.62 ± 0.08 mg QE/g) and TFC (160.48 ± 0.08 mg GAE/g) was reported highest for the most polar solvent i.e. ethyl acetate. The in vitro antioxidant study disclosed highest IC50 value for ethyl acetate (2.15 mg/mL), queued by chloroform (1.19 mg/mL) and hexane (0.89 mg/mL), displaying that polar solvents are good extraction solvents for the identification of free radical scavenging properties, TFC and TPC.